2010
DOI: 10.3233/jad-2010-100705
|View full text |Cite
|
Sign up to set email alerts
|

Does Inorganic Mercury Play a Role in Alzheimer's Disease? A Systematic Review and an Integrated Molecular Mechanism

Abstract: Abstract. Mercury is one of the most toxic substances known to humans. It has been introduced into the human environment and has also been widely used in medicine. Since circumstantial evidence exists that the pathology of Alzheimer's disease (AD) might be in part caused or exacerbated by inorganic mercury, we conducted a systematic review using a comprehensive search strategy. Studies were screened according to a pre-defined protocol. Two reviewers extracted relevant data independent of each other. One thousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 161 publications
3
117
2
3
Order By: Relevance
“…When Hg 0 from dental amalgams ( Fig. 1 ) is inhaled as a vapor into the lungs, about 80% is absorbed (Schafer et al 1999 ;Mutter et al 2010 ). Due to its uncharged monoatomic form, Hg 0 is highly diffusible and lipid soluble, and easily crosses the blood-brain barrier and lipid bilayers of cells ( Opitz et al 1996 ).…”
Section: Absorption Distribution and Toxicity Of Mercurymentioning
confidence: 99%
See 2 more Smart Citations
“…When Hg 0 from dental amalgams ( Fig. 1 ) is inhaled as a vapor into the lungs, about 80% is absorbed (Schafer et al 1999 ;Mutter et al 2010 ). Due to its uncharged monoatomic form, Hg 0 is highly diffusible and lipid soluble, and easily crosses the blood-brain barrier and lipid bilayers of cells ( Opitz et al 1996 ).…”
Section: Absorption Distribution and Toxicity Of Mercurymentioning
confidence: 99%
“…However, inorganic mercury is excreted largely via urine and feces, and partially through sweat, tears and breast milk and cell organelles, such as mitochondria. Mercury vapor also penetrates the mucosa and connective tissue of the oral and nasal cavities and may be transported into nerve cells (Mutter et al 2010 ).…”
Section: Absorption Distribution and Toxicity Of Mercurymentioning
confidence: 99%
See 1 more Smart Citation
“…The most important neurotoxic effects of aluminum and lead are their ability to trigger the formation of senile plaques and neurofibrillary tangles, to cause failure in neurotransmission and the induction of oxidative stress [7,54]. Alternatively, it has been demonstrated that the exposure to mercury and arsenic induces the appearance of characteristic pathological hallmarks of AD, including the formation of amyloid deposits, hyperphosphorylation of protein tau, disruption of redox regulation and inflammation, among others [55][56]. In addition, lead and cadmium cause a reduction in the brain content of acetylcholine [57][58], an important neurotransmitter closely related to the pathogenesis of AD.…”
Section: The Biological Importance Of Metalsmentioning
confidence: 99%
“…Increased mercury concentrations have been reported in brain regions in some patients with AD. In in vitro and animal experiments, low levels of inorganic mercury did cause AD-typical nerve cell degeneration [15] . The increased risk in subjects with APOE 4 may be due to its reduced ability to bind heavy metals [15] .…”
Section: Introductionmentioning
confidence: 97%